Acupuncture Treatment for Hypotension Patients at Bale Terapi Datu (TCM Center NTB), West Lombok Regency - Lalu Budyawan; Mayang Wulandari; Ikhwan Abdullah; Leny Candra Kurniawan (Jurnal Indonesia Sosial Sains, 2026)
Low blood pressure (hypotension) is a condition in which blood pressure is lower than 90/60 mmHg or low enough to cause symptoms such as dizziness and fainting. Acupuncture therapy offers an approach to addressing low blood pressure or hypotension without the side effects of pharmaceutical blood-pressure-raising medications. This study aims to evaluate the effectiveness of acupuncture treatment for hypotension patients at Bale Terapi Datu (TCM Center NTB) in West Lombok Regency. This single case study involved eight therapy sessions with a 31-year-old female participant who had been experiencing hypotension for the past two weeks. Data collection included observation, interviews, hearing, smell, and touch, following Traditional Chinese Medicine (TCM) diagnostic standards. Acupuncture points were chosen based on a diagnosis of qi and xue deficiency, with needle manipulation focused on tonification. After eight therapy sessions, the participant experienced significant improvement in blood pressure from 70/80 mmHg to 100/80 mmHg. Additional symptoms such as dizziness, fatigue, constipation, insomnia, loss of appetite, and restlessness have significantly decreased, and the participant’s physical condition has improved. Tongue examination revealed increased redness, and the pulse, which was initially weak, became more stable, indicating a smoother flow of liver qi and blood. The acupuncture treatment provided was effective in treating low blood pressure or hypotension caused by qi and blood deficiency by improving qi flow and increasing blood volume and circulation, thereby improving physical condition and reducing the symptoms experienced by the participant.